Self-Introspection as an Idea in Creating Paintings - Kepakisan, Gede Agung Nugraha Arya; Yudha, I Made Bendi; Kondra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
This thesis contains a description of the creation of works of painting with the theme "Self-Introspection as an Idea in Creating Works of Painting". This thesis discusses the significance of introspecting oneself on past mistakes in order to achieve a more positive impact in the future. Self-examination enables learning from mistakes, personal improvement, self-development, improved social relationships, and increased mental well-being. In conclusion, self-introspection is an important step on the journey towards better personal development and achieving a more positive impact in the future. The results of the application of the past are felt through the five senses, reason and true feelings which combine harmoniously and the more aware you are, the more you understand the life scenario. This is the grand design to bring us to continue evolving towards perfection.